Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Mid-Atlantic)--Softshell clam - Abraham, Barbara J.; Dillon, Perian L. (Washington U.S. Department of the Interior, 1986)
U.S. Fish Wildl. Serv. Biol. Rep. 82(11.68)
Keywords: Invertebrates; Fishes; History; Softshell clam--Mid Atlantic